Oxygen vacancies effect on phase separation in Pr0.5Ca0.2Sr0.3MnO3-δ - Niebieskikwiat, Dario Gabriel (2003)
We study the effect of the introduction of a controlled amount of oxygen vacancies on the magnetic and transport properties of the phase separated manganite Pr0.5Ca0.2Sr0.3MnO3−δ, for δ=0 and 0.01. This compound presents a paramagnetic to ferromagnetic (FM) transition below TC∼240 K, and then to a charge-ordered (CO) and antiferromagnetic (AFM) phase at TCO∼175 K. However, below TCO an appreciable FM component (∼20%) still survives, related to a FM volume immersed within the CO/AFM matrix. At low temperatures, in the mainly CO phase, the introduction of oxygen vacancies enhances the FM ordering, with the consequent decrease of resistivity and magnetoresistance (MR). On the contrary, in the FM phase (in the range TCO<T<TC) the magnetization is reduced and the resistivity and MR increase. These results are discussed in the frame of percolative transport in metal–insulator mixtures, and frustrated double exchange interaction due to the interruption of some Mn–O–Mn chains.